Memorandum of understanding between Universiti Teknologi MARA and PS Food & Beverage Sdn Bhd / Fakulti Komunikasi dan Pengajian Media - Universiti Teknologi MARA, Fakulti Komunikasi dan Pengajian Media (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.